Management of Chronic Obstructive Pulmonary Disease: An Update (Bangladesh Journal of Medicine, 2026)
Chronic obstructive pulmonary disease (COPD) remains a leading cause of morbidity and mortality globally and is driven mainly by smoking, indoor biomass exposure, and air pollution. Despite advances in inhaled therapy, many patients continue to experience exacerbations and poor quality of life. This narrative review summarizes recent updates in pharmacologic and nonpharmacologic management drawn from major randomized trials, meta-analyses, and guidelines published between 2010 and 2025. The evidence supports early combination and triple-inhaler therapy to reduce exacerbations, improve lung function, and lower mortality, particularly in eosinophilic COPD patients. Novel biologics, such as mepolizumab and dupilumab, result in meaningful reductions in moderate or severe exacerbations, whereas new agents, such as roflumilast and ensifentrine, benefit frequent exacerbators with chronic bronchitis. Nontarmacologic measures, including smoking cessation, pulmonary rehabilitation, vaccination and high-intensity noninvasive ventilation, remain essential components of comprehensive care. In resource-limited settings such as Bangladesh, barriers to diagnosis, cost, and access to inhalers highlight the need for affordable generics, local rehabilitation programs, and the integration of COPD services into primary care. The evolving therapeutic landscape now enables more personalized, phenotype-driven management. Continued research and the adaptation of global evidence to local contexts are critical for reducing the COPD burden and improving long-term outcomes.Bangladesh J Medicine 2026; 37(2): 86-91